Design of efficient full‐rate linear dispersion space‐time block codes over correlated fading channels. Issue 12 (1st August 2013) - Kuhestani, Ali; Azmi, Paeiz
Abstract : In this study, the authors present a method to design efficient full‐rate linear dispersion space‐time block codes (LD‐STBCs) in correlated Rayleigh fading channels with simple detection at the receiver. The authors first derive a formula for the achievable capacity of an LD‐STBC coded multi‐input multiple‐output (MIMO) system as a function of correlation at the transmitter and the receiver. Moreover, the authors compute closed‐form bit‐error rate equations for multiple phase shift keying ( M ‐PSK) and multiple quadrature amplitude modulation ( M ‐QAM) schemes. Then, the authors present a method to construct LD‐STBCs over correlated Rayleigh fading MIMO channels. Finally, the authors design LD‐STBCs for two and four transmit antennas. The designed LD‐STBCs enjoy full‐rate, minimum power fluctuation, simple structure, simple processing at the receiver. Moreover, the designed LD‐STBCs for two transmit antennas provide better performance than Alamouti and LYC codes and the designed LD‐STBCs for four transmit antennas provide better performance than TV codes at practical signal‐to‐noise ratios. Simulation results show that when the proposed LD‐STBC for two transmit antennas is concatenated with an efficient outer channel encoder, it provides better performance than LYC code over correlated fading channels.